FORMULASI DAN UJI IN VITRO NILAI SPF KRIM TABIR SURYA EKSTRAK KULIT BUAH NANAS MADU (Anana comosus L. Merr) - Wimzy Rizqy Prabhata; Alfa Salsabila, Pradini; Wulandari, Fitri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Excessive UV exposure from sun causes negative impacts on the skin. Honey pineapple peel (Anana comosus L. Merr) is known to contain flavonoid and tannin that absorb UV light. This study reports the activity of sunscreen in cream preparations of 96% ethanolic extract of honey pineapple peel along with its physical characteristics and stability test results. Honey pineapple peel was soxhleted using 96% ethanol. The extract was then formulated into a cream using various concentrations of cream base: stearic acid (8-12%) and triethanolamine (2-4%) generating three formulas. The cream was then tested for its physical characteristics, physical stability, and sunscreen activity. The SPF value of extract at concentrations of 10%, 20%, and 30% respectively were 28.38; 31.05; and 35.12. The physical characteristics of the cream were brown in color, semisolid in shape, have a distinctive smell, homogeneous; with pH value, adhesion capability and spreadability that meet the cream requirements. Of the three formulas, formula I has the best pH stability, adhesion capability and spreadability. The results of SPF value of each cream formula: F1 (34.54); F2 (34.35) and F3 (34.27). This study demonstrated that the 96% ethanolic extract of honey pineapple peel can be formulated into cream dosage form and has a good sunscreen activity.